2019
DOI: 10.1371/journal.pone.0216949
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Ebola glycoprotein into HIV particles facilitates dendritic cell and macrophage targeting and enhances HIV-specific immune responses

Abstract: The development of an effective vaccine against HIV infection remains a global priority. Dendritic cell (DC)-based HIV immunotherapeutic vaccine is a promising approach which aims at optimizing the HIV-specific immune response using primed DCs to promote and enhance both the cellular and humoral arms of immunity. Since the Ebola virus envelope glycoprotein (EboGP) has strong DC-targeting ability, we investigated whether EboGP is able to direct HIV particles towards DCs efficiently and promote potent HIV-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

6
0

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…Another study also checked for the impact of EBOV GP without MLD (EBOV GP ΔMLD) on the stimulation of anti-GP and neutralizing antibodies; this study revealed that EBOV GP ΔMLD elicits more anti-EBOV GP antibody than EBOV GP VLP, with moderate stimulation of neutralizing antibodies [107], indicating that MLD is dispensable for EBOV attachment. Our study also showed that the removal of MLD from EBOV facilitates the cell entry efficiently more than the wild type; however, EBOV GP wild-type stimulated NFκB than EBOV GP with deleted MLD [115]. Moreover, in the development of drugs for EBOV, EBOV GP is an important target to be considered.…”
Section: Ebov Gp: Bane or Benefitmentioning
confidence: 75%
See 4 more Smart Citations
“…Another study also checked for the impact of EBOV GP without MLD (EBOV GP ΔMLD) on the stimulation of anti-GP and neutralizing antibodies; this study revealed that EBOV GP ΔMLD elicits more anti-EBOV GP antibody than EBOV GP VLP, with moderate stimulation of neutralizing antibodies [107], indicating that MLD is dispensable for EBOV attachment. Our study also showed that the removal of MLD from EBOV facilitates the cell entry efficiently more than the wild type; however, EBOV GP wild-type stimulated NFκB than EBOV GP with deleted MLD [115]. Moreover, in the development of drugs for EBOV, EBOV GP is an important target to be considered.…”
Section: Ebov Gp: Bane or Benefitmentioning
confidence: 75%
“…Also, Venezuelan Equine Encephalitis (VEE), virus-like replicon particles with the replacement of VEE virus structural genes by EBOV GP or NP, has been demonstrated to have full protection against Ebola virus challenge [171]. Interestingly, our recent study showed that the incorporation of EBOV GP into the HIV VLP induces a more effective immune response against HIV-1 [115]. We showed that the presence of EBOV GP enhances the ability of the HIV VLP to target MDMs and MDDCs.…”
Section: Ebola Gp-targeting Dcs Can Facilitate Immune Responses Fomentioning
confidence: 99%
See 3 more Smart Citations